A Sweet Warning: Mucin-Type O-Glycans in Cancer - Yuhan Zhang; Lingbo Sun; Changda Lei; Wenyan Li; Jiaqi Han; Jing Zhang; Yuecheng Zhang (Cells, 2022)
Glycosylation is a common post-translational modification process of proteins. Mucin-type O-glycosylation is an O-glycosylation that starts from protein serine/threonine residues. Normally, it is involved in the normal development and differentiation of cells and tissues, abnormal glycosylation can lead to a variety of diseases, especially cancer. This paper reviews the normal biosynthesis of mucin-type O-glycans and their role in the maintenance of body health, followed by the mechanisms of abnormal mucin-type O-glycosylation in the development of diseases, especially tumors, including the effects of Tn, STn, T antigen, and different glycosyltransferases, with special emphasis on their role in the development of gastric cancer. Finally, tumor immunotherapy targeting mucin-type O-glycans was discussed.